Fire effects in a landscape of fear : food availability and perceived predation risk as potential determinants of patch utilization by herbivore prey - Kymmell, David (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2019)
Context: A major effect of climatic change is the global increase in forest fires, which potentially creates an increase in food availability for herbivorous species. Also vegetation density and the numbers of tree logs increase in burned sites, and this is thought to influence the perceived risk of herbivore prey species, which affects their anti‐predator behaviour and thereby the patch utilization. This cascading effect of forest fires might have implications on future ecosystem functioning in the burned area, and more knowledge about the effects of landscape features on predator‐prey interactions is needed to adapt conservation and wildlife management policies, to the changing climate.